X^2(x+4) x 3x^2(x-1)
(X^3+4x^2) x (3x^3 -3x^2)
3x^6 -3x^5+12x^5 -12x^4
3x^6 +9x^5-12x^4
I think that’s how you do it
Answer:M=24
Step-by-step explanation:
What do you mean by Social Contract?
The product of a scalar and a matrix is found by multiplying each element of the matrix by the scalar. Multiply each element by -4.
... [4 -12 -24 12]
A.) 7^4x = 10
log base 10 (7^4X) = log base 10 (10)
4x log base 10 (7) = 1
4x (0.8451) = 1
3.3804x = 1
x = 0.2958
b.) ln(2) + ln(4x-1) = 5
ln (2 * 4x-1) = 5
ln (8x-2) = 5
log base (3) (8x-2) = 5
e^5 = 8x-2
e^5+2 = 8x
x = 18.8016